Development of Array-Based Gold Nanoclusters for Discrimination of CA125 Overexpressed Serum Samples - Yi Shi (Hindawi Limited, 2021)
Here, we reported a simple method for recognizing CA125 overexpressed serum samples using array-based fluorescent gold nanoclusters (AuNCs). The sensing array was fabricated by the combination of various CA125 aptamer functionalized AuNCs. The fluorescence of different aptamer-capped AuNCs was quenched to a different extent in the presence of CA125. By comprehensive analysis of these fluorescence changes, unique patterns were formed when CA125 was overexpressed in serum samples. This strategy is successfully used for discriminating CA125 overexpressed human serum samples, which have great importance for the diagnosis of ovarian cancer in the early stage.